PENGEMBANGAN IRIGASI, PRODUKSI PANGAN DAN IMPLIKASIN TERHADAP SIKLUS AIR (Irrigation Development, Food Production and Their Implicatior to the Hydrological Cycles) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Abstract The cereal production especially rice has increased sharply in Indonesia. The irrigation development program implemented by the government has become an important rote in the production process. However, expansion of irrigated paddy lands significantly influence the hydrological regime in its basin. A set of basic indicator for assessing the hydrological implication of the development in a river basin was proposed.